Indicator-based Sustainability Assessment of the German Energy System and its Transition - Rösch, ChristineBräutigam, Klaus-RainerKopfmüller, JürgenStelzer, VolkerLichtner, PatrickFricke, Annika (KIT Scientific Publishing, 2018)
The energy transition not only has an impact on technical infrastructures but also leads to socio-economic changes. To evaluate the sustainability aspects of the German Energiewende, the authors have developed a monitoring system which includes 45 indicators and their corresponding target values for 2020, 2030, and 2050 as well as a rating system for the year 2020 based on a distance-to-target approach and traffic color lights.